Genetic analysis of hypermelanosis in Chinese tongue sole (Cynoglossus semilaevis) - Yao, Na; Zhang, Yaqun; Li, Yangzhen; Hu, Yuanri; Li, Hengde (Frontiers in Marine Science, 2022)
Chinese tongue sole (Cynoglossus semilaevis) is an economically important marine fish in China. Generally, the eyeless side of the Chinese tongue sole is white and the side with eyes is brown after metamorphosis, hypermelanosis may still occur in the eyeless side in certain individuals after metamorphosis, which greatly decreases consumer acceptance and market price. In order to study the possibility of genetic improvement, we determined genomic markers in Chinese tongue sole using the genotyping-by-sequencing method and analyzed their association with hypermelanosis area. Genetic analysis showed that hypermelanosis was a complicated quantitative trait, and the estimated heritability for hypermelanosis incidence and area ratio were 0.16 and 0.21, respectively. Genomic selection analysis showed that selection based on hypermelanosis incidence and area ratio had similar reliabilities and prediction accuracies, indicating the feasibility of genetic improvement. Nine loci were significantly associated with hypermelanosis, few of which included genes or flanked genes potentially associated with skin disease, indicating the potential complicated genetic mechanisms underlying hypermelanosis in the Chinese tongue sole.